Digitales Zentralbankgeld: Dabei sein ist nicht alles - Stefan Schäfer (Wirtschaftsdienst, 2023)
– The European Central Bank (ECB) wants to push ahead with the "digital euro" project. However, the digital euro is by nomeans the only and possibly not even a good (let alone the best) way to respond to the comprehensive change in the world of money. Interms of its reputation, the ECB must act with the utmost caution. Instead of launching its own project on the market in just a few years,the ECB would be well advised to take a step back and support a competition of ideas that is open to all technologies.
Keywords: E42; E51; E58; 330; Digitales Zentralbankgeld; Digitales Zentralbankgeld